Competency-Based Talent Management and Psychological Outcomes in State Owned Enterprises - Marianggodo, Wahyu Dodi Tri; Putra, Muhammad Ghazali Bagus Ani (PT. Anagata Sembagi Education, 2025)
This study aims to explore the implementation of competency-based talent management and its impact on employee psychological outcomes in State-Owned Enterprises (SOEs). The research method used is a qualitative case study design, through in-depth interviews, focus group discussions (FGDs), and document analysis, with purposive selection of informants involving HR managers, unit leaders, and employees participating in the talent management program. The results show that the implementation of competency-based talent management has a positive effect on motivation, job satisfaction, and organizational commitment. The main supporting factors include management support, career path transparency, and a merit-based organizational culture. However, obstacles that arise include long bureaucracy, limited resources, and nepotism practices. This study confirms that the effectiveness of competency-based talent management is not only related to organizational performance, but also contributes significantly to employee psychological well-being.